ETHMALOSA FIMBRIATA AND CHRYSICHTHYS MACROPOGON AS BIO-INDICATORS OF HEAVY METAL IN FOUR COASTAL TOWNS OF ILAJE LGA, ONDO STATE, NIGERIA - Ojo, Oluwasola Busuyi; Olawusi-Peters, Olamide Olaronke; Ajibare, Adefemi Olatayo (FUDMA JOURNAL OF SCIENCES, 2025)
This study aimed to assess the accumulation level of Cadmium (Cd), Zinc (Zn), Lead (Pb), Copper (Cu), Iron (Fe), and Manganese (Mn) in two organs (gills and muscle) of two fish species (Ethmalosa fimbriata and Chrysichthys macropogon) from four coastal towns (Ayetoro, Bijimi, Idiogba and Asumogha) of Ilaje Local Government Area, Ondo State, Nigeria. Fish samples used were collected monthly for a period of four months in the four stations using the gillnet with mesh sizes of 0.6cm, 1.0cm, 2.0cm, 3.0cm and 4.0cm throughout the period of study. The samples were digested and heavy metal concentration was analyze using Atomic Absorption Spectrophotometer (Model AA240FS). Concentrations of heavy metal in both species occurred in the order: Fe>Mn>Zn>Cu>Pb>Cd. Heavy metal concentration was higher in the gills compared to muscles where metabolic activity is relatively lower. Lead concentration in the samples across the four stations varied from 0.328 to 0.923 mg/kg. Concentrations of Zn in samples of the two fishes ranged from 1.644±0.53 to 2.095±0.26 while cadmium concentrations in muscle and gill of E. fimbriata varied from 0.003±0.00 to 0.355±0.41. Bio-accumulation of metal in E. fimbriata and C. macropogon from the study area shows aquatic pollution.